Human herpesvirus-6 entry into the central nervous system through the olfactory pathway - Harberts, Erin; Yao, Karen; Wohler, Jillian E; Maric, Dragan; Ohayon, Joan; Henkin, Robert; Jacobson, Steven (Proceedings of the National Academy of Sciences - PNAS, 2011)
Viruses have been implicated in the development of neurodegenerative diseases, such as Alzheimer's, Parkinson's, and multiple sclerosis. Human herpesvirus-6 (HHV-6) is a neurotropic virus that has been associated with a wide variety of neurologic disorders, including encephalitis, mesial temporal lobe epilepsy, and multiple sclerosis. Currently, the route of HHV-6 entry into the CNS is unknown. Using autopsy specimens, we found that the frequency of HHV-6 DNA in the olfactory bulb/tract region was among the highest in the brain regions examined. Given this finding, we investigated whether HHV-6 may infect the CNS via the olfactory pathway. HHV-6 DNA was detected in a total of 52 of 126 (41.3%) nasal mucous samples, showing the nasal cavity is a reservoir for HHV-6. Furthermore, specialized olfactory-ensheathing glial cells located in the nasal cavity were demonstrated to support HHV-6 replication in vitro. Collectively, these results support HHV-6 utilization of the olfactory pathway as a route of entry into the CNS.